New taxa of Orthoptera (Insecta Tettigoniidae Phaneropterinae) from Madagascar - Massa, Bruno (Zootaxa, 2017)
The author reports the results of a study on Orthoptera collected in Madagascar and preserved in two European Natural History museums. He describes Symmetroraggea depravata n. sp., Parapyrrhicia longipodex n. sp., Madagascarantia bartolozzii n. gen. n. sp., Mimoscudderia spinicercata n. sp. In addition, he lists new records or unknown taxonomical characters of Xenodus nobilis Carl, 1914 and Parapyrrhicia virilis Carl, 1914.